PENERAPAN MEDIA PEMBELAJARAN LUPER (LUDO PERUBAHAN ENERGI) BERBANTUAN SOAL AKM KELAS SEBAGAI UPAYA PENINGKATAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN JATISARI SEMARANG - Juwita Fitria Puspitasari; Panca Dewi Purwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading literacy ability is one of the basic skills that must be developed since elementary school because it is an important foundation in the educational process and progress of a nation. Reading comprehension, as part of reading literacy, helps students understand and apply information from reading. However, students' low reading interest and limited reading comprehension abilities often become obstacles in understanding learning material. This research aims to describe the application of the Luper learning media (Ludo Energy Changes) assisted by class AKM questions and test the effectiveness of the Luper media in improving students' reading comprehension skills. This research uses a combination method (Mix Method) to combine qualitative and quantitative approaches. A qualitative approach was carried out through interviews with teachers and student observations during the application of ludo learning media assisted by AKM questions. The quantitative approach uses a one group pretest-posttest design to measure the effectiveness of learning media. The research results show that the learning media Luper (Ludo Changes in Energy) assisted by class AKM questions is effective in improving students' reading comprehension. Media is applied at the stage of analyzing and evaluating the problem solving process in the Problem-Based Learning (PBL) learning model. The average pretest-posttest score showed an increase from 56.92 to 83.82. The N-Gain test results obtained a value of 0.63 with medium criteria. Overall, it can be concluded that the application of the Luper learning media (Ludo Changes in Energy) assisted by class AKM questions is effective in improving students' reading comprehension skills.